Návrh projektu vývoje transakce do modulu finančního účetnictví systému SAP - Krejza, Matěj (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce se zaměřuje na návrh projektu vývoje transakce do modulu finančního účetnictví systému SAP. Práce se skládá z teoretických východisek na jejichž základě je vypracovaná analýza současného stavu a vlastní návrhy řešení. Výsledkem bakalářské práce je dokument, podle něhož lze postupovat při samotné realizaci projektu.

The bachelor thesis focuses on the design of a transaction development project for the financial accounting module of the SAP system. The thesis consists of theoretical background on the basis of which the analysis of the current state and the actual solution proposals are made. The result of the bachelor thesis is a document according to which the actual implementation of the project can be followed.
Project Proposal for the Development of a Transaction in the Financial Accounting Module of the SAP System
Keywords: Projektové řízení; SWOT analýza; logický rámec; Ganttův diagram; WBS; Project management; SWOT analysis; logical framework; Gantt chart; WBS